A SAS macro for computing statistical tests for two-way table and stability indices of nonparametric method from genotype-by-environment interaction (Acta Scientiarum. Agronomy, 2016)
Genotype-by-environment interaction refers to the differential response of different genotypes across different environments. This is a general phenomenon in all living organisms and always has been one of the main challenges for biologists and plant breeders. The nonparametric methods based on the rank of original data have been suggested as the alternative methods after parametric methods to analyze data without perquisite assumptions needed for common analysis of variance. But, the lack of statistical software or package, especially for analysis of two-way data, is one of the main reasons that plant breeders have not greatly used the nonparametric methods. Here, we have explained the nonparametric methods and presented a comprehensive two-parts SAS program for calculation of four nonparametric statistical tests (Bredenkamp, Hildebrand, Kubinger and van der Laan-de Kroon) and all of the valid stability statistics including HÃ¼hn’s parameters (Si(1), Si(2), Si(3), Si(6)), Thennarasu’s parameters (NPi(1), NPi(2), NPi(3), NPi(4)), Fox's ranking technique and Kang’s rank-sum.